2022
DOI: 10.17507/jltr.1303.06
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Saudi Students About Non-Native English Teachers and Native English Teachers in Teaching English at Jazan University

Abstract: This study tries to investigate the perception of Saudi students at Jazan University about native English-speaking teachers (NEST) and non-native English-speaking teachers based on their teaching the language skills and grammar. The perception of 50 native English-speaking teachers and 50 non-native English teachers was collected from the students taught by these teachers. The findings show that native English-speaking teachers are outstanding at teaching reading, listening and speaking. In contrast, non-nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Davies (2013) argued that the ability to teach is crucial in a language instructor, and mastery of the written form of the language is paramount among other features. Haque and Sharmin (2022) found that NESTs outstripped NNESTs in the four skills, while NNESTs were better at teaching grammar.…”
Section: B Native and Non-native English Language Instructors In High...mentioning
confidence: 92%
“…Davies (2013) argued that the ability to teach is crucial in a language instructor, and mastery of the written form of the language is paramount among other features. Haque and Sharmin (2022) found that NESTs outstripped NNESTs in the four skills, while NNESTs were better at teaching grammar.…”
Section: B Native and Non-native English Language Instructors In High...mentioning
confidence: 92%
“…In the past, there was a trend of high demand of native teachers to teach English. It was believed that native teachers are the best teachers to teach to the learners (Haque, & Sharmin, 2022). After the long practice people realized that language cannot be separated from culture and teaching language means teaching culture and the native teachers failed to mix the culture in language classes as a result it couldn't carry to the learners in the depth of the matter, therefore now a days the demand of nonnative teachers is increasing rather than native teachers.…”
Section: Demand Of Nonnative English Speaker Teachermentioning
confidence: 99%
“…This study characterizes the phenomenon of how context exerts a cross-sectional influence on language students' perceptions of teachers with respect to the development of L2 identity in students. Haque and Sharmin (2022) conducted a study to explore the notion that instructors who are proficient in English as their first language are more effective in facilitating the development of reading, listening, and speaking abilities. Conversely, individuals who are not native speakers of the English language possess exceptional aptitude as instructors of grammar, reading, and writing.…”
Section: Introductionmentioning
confidence: 99%